The Travel Photography Book - Kelby, Scott (Rocky Nook, 2021)
Learn how to take professional-quality photographs when you travel, using the same tricks today's top photographers use! Whether you're on a dedicated photo trip or a family vacation, you want to come home with a collection of great photos to show your friends, share online, and even make a large print for your home. Capturing great travel photographs can be tricky...but not if you know the secrets that Scott Kelby is here to share with you! Here's how Scott describes this book's brilliant premise: "If you and I were out shooting, and you asked me, 'Hey, how do I get this flower to be in focus, with the background out of focus?,' I wouldn't stand there and give you a photography lecture. In real life, I'd just say, 'Put on your zoom lens, set your f-stop to f/2.8, focus on the flower, and fire away.' That's what this book is all about: you and I out shooting where I answer questions, give you advice, and share the secrets I've learned just like I would with a friend--without all the technical explanations and techie photo speak." This isn't a book of theory--full of confusing jargon and detailed concepts. This is a book on which button to push, which setting to use, and when to use it. With 200 of the most closely guarded "tricks of the trade" for travel photographers, this book gets you shooting dramatically better-looking, sharper, more colorful, more professional-looking travel photos every time. Each page covers a single concept that makes your photography better. Every time you turn the page, you'll learn another pro setting, tool, or trick to transform your work from snapshots into gallery prints. If you're tired of taking shots that look "okay," and if you're tired of looking in photography magazines and thinking, "Why don't my shots look like that?" then this is the book for you. TABLE OF CONTENTS Chapter 1: Research Chapter 2: What Makes a Great Travel Photo? Chapter 3: Photographing People Chapter 4: Gear and Settings Chapter 5 Travel Photography Accessories Chapter 5: Composition Chapter 6: Other Cool Stuff to Shoot Chapter 7: When to Use Your Phone Instead Chapter 8: What to Shoot (and What to Skip) Chapter 9: Sharing Your Trip Chapter 10: Travel Tips & Tricks Chapter 11: Post-Processing Tips Chapter 12: Travel Photo Recipes.